The effect of artificial lighting and controls on patient outcomes in behavioral health facilities - Radina, Gabriella Faith (Kansas State University, 2022)
Mental illness has been somewhat of an enigma for much of human history. Lack of understanding mental illness led to inhumane treatments in psychiatric hospitals. During the era of inhumane patient treatment, it was theorized that the built environment could influence patient behavior and reception to treatment. Subsequently, design recommendations for mental health treatment facilities in the 18th century were centered around daylighting allowances which has significant benefits including regulating hormones and mental health. With the advent of artificial light sources, humans can control how much light they consume, which can be deleterious to biological systems including the circadian system. This report provides design recommendations for patient rooms, group rooms, and corridors in an adult, behavioral health, inpatient hospital setting with an LED lighting system. The design recommendations are based on studies that examine the impact of lighting on various mental illnesses (depression, eating disorders, bipolar disorder, and schizophrenia) within a lens of the biological impact of current lighting solutions. To ensure proper circadian entrainment, a circadian lighting system should be installed. In patient rooms, an exam luminaire above the bed may be provided with supplemental lighting throughout the room in the form of downlights. Controls may be provided outside of the patient room. Task lighting in patient and group rooms should be provided via wall surface-mount touch-controlled fixtures. Additionally, group rooms should have lighting that is controllable by patients via dimming or multi-level stepped dimming. Corridors must consider patient viewing, so cove lighting along the perimeter of the ceiling provides uniform ceiling distribution while eliminating glare. Throughout a behavioral health facility, wall- recessed wayfinding luminaires installed 2’ above the finished floor with a light source at 2700K should provide evening illuminance. Melanopic lux measurements can be a useful way to quantify the impact of lighting on biological processes. The lighting designer should discuss the spectral power distribution with the manufacturer to ensure that the blue wavelength light decreases as correlated color temperature decreases. Providing appropriate lighting solutions can decrease the length of patient stays and increase staff productivity.
Keywords: Intrinsically photosensitive retinal ganglion cell (ipRGC); Circadian lighting; Light and health; Circadian rhythms; Behavioral health